Flexible and free-standing reduced graphene oxide thick films with PMMA stabilized silver nanoparticles, as a potential probe for cancer thermal therapy - Asha, S.; Nimrodh Ananth, A.; Jose, S. P.; Rajan, M. A. J. (Biomedical physics and engineering express, 2018)
hermal therapy is an efficient, cost-effective method for treating different types of cancers and hence flexible, light weight, biocompatible heating materials with low power consumption are of utmost importance. Partially reduced flexible, robust and bio-compatible thick graphene oxide films with, mostly edge functionalized Polymethyl methacrylate (PMMA) and in situ grown silver nanoparticles were prepared using simple soak and dry strategy. Larger distribution of silver nanoparticles with a mean diameter of 2.5 nm were anchored towards the edges of these thick films. The electrothermal (Joule heating) performance were found to increase in the presence of silver nanoparticles due to decrease in sheet resistance (0.33 × 104 Ωm) and increase in electron-phonon interaction. These free-standing, flexible films exhibited stable Joule heating behavior under repeated voltage on/off cycles. In-vitro studies performed on breast cancer cells in the presence of the prepared films, with an external applied voltage of 10 VDC, shows 67% cell death. This work proves the potentiality of thick heterogeneous (partially) reduced graphene oxide films towards site specific destruction of solid tumors by utilizing its Joule heating properties.

Surface colonized silver nano particles over chitosan poly-electrolyte micro-spheres and their multi-functional behavior - Prakash, B. (Materials Research Express, 2018)
hitosan/tripolyphosphate polyelectrolyte (TPP) microspheres, decorated and surface functionalized with silver nanoparticles (NPs) of average diameter of 15 nm, were synthesized following a simple two-step procedure. These Ag NP-functionalized polyelectrolyte microspheres (Ag-CSPMs) are found to be biocompatible and enhancing the reactive oxygen species in curcumin with excellent anti-bacterial activity for selected Gram-positive and negative bacterial strains, making them much attractive relative to bare surface counterparts; the well-stabilized silver NPs do not form any agglomerations on the surface of the chitosan microspheres. They also show excellent cytotoxic behavior towards MCF7 cell lines, showing a half-maximal inhibitory concentration (IC50) of 32 μg ml-1. Therefore, Ag-CSPMs exhibit multi-functional ability having potential towards theranostics applications.
Keywords: antibacterial properties; Chitosan; Cytotoxicity; reactive oxygen species; silver nanoparticles; theranostics